Natural Cats - Madsen, Chris; Illustrated by Naumann, Anuk (London Gaia Books Limited, 1997)
This is a comprehensive guide to caring for cats. It covers all aspects of cat behaviour and ownership, and provides environmental tips for cat owners. Detailed charts list common ailments, their symptoms and the available treatments. Additional charts deal with parasitic worms and flea control.
Include colour illustrations and index
Veterinary Consultant by Thomas, Ken
Keywords: Cats -- Cats--Behavior -- Cats--Health